Psychological Expenditure and its Relationship to the Serving Skills of Specialized Volleyball Players - Mohammed, Mohammed Munther; Naser, Mudher Ali (Pubmedia Jurnal Pendidikan Olahraga, 2025)
The importance of this research lies in developing a psychological expenditure scale and its relationship to the passing skills of specialized volleyball players. The research problem focused on psychological expenditure as one of the problems and challenges faced by specialized players and its negative impact, such as poor skill performance, which is reflected in the performance of the player and the team. This weakens the player's self-confidence and concentration and affects the team's performance in tournaments as well as their performance in training. The research aims to develop a psychological expenditure scale, and the researcher used the descriptive approach as it is appropriate for the nature of the research problem. The five axes of the scale are (emotional numbness, lack of sense of achievement - emotional stress - poor communication with teammates - physical effects). The scale was weighted on a five-point scale and consisted of 30 items, most of which were negative. The sample consisted of 140 players from specialized schools in Baghdad, Dhi Qar, Anbar, Maysan, Wasit, and Basra for the period from March 1, 2025, to May 1, 2025. The data was statistically processed using the SPSS statistical program, using the T-test for independent samples in the discriminative ability of the statements and Pearson's correlation for internal consistency. The researcher concluded that there is a significant relationship between psychological expenditure and serving skill, and that psychological pressure and Psychological and physical fatigue among players must be reduced.